TECHNOLOGY OF DEVELOPMENT OF FACTORS INFLUENCING ACTIVE TEACHING METHODS - Ismoilova Mashhura Eshmamat kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the factors influencing the effectiveness of active teaching methods and pedagogical technologies aimed at their development. The study highlights the role of active methods in the modern educational process, their interrelation with didactic, psychological and organizational factors. Also, technological approaches that serve to increase the effectiveness of active teaching methods are identified, and their impact on the quality of education is explained on a scientific basis. The results of the study serve to expand the possibilities of effective use of active teaching methods in pedagogical practice.